A critical overview of the current myofascial pain literature – July 2016. Issue 3 (July 2016) - Dommerholt, Jan; Grieve, Rob; Finnegan, Michelle; Hooks, Todd
Summary: The overview of the myofascial pain literature includes a wide variety of basic and clinical studies, ranging from assessing muscle activation patterns to the impact of platelet-rich plasma injections. Contributions to the literature once again came from all corners of the world, such as Australia, Belgium, Brazil, Germany, Greece, Iran, Italy, Japan, Korea, the Netherlands, Norway, Poland, Spain, Taiwan, Turkey, and the USA. A total of 30 papers are included in this overview.